Nurturing wellbeing in academia : how to prioritise your mental health - Gibson, Poppy (Surviving and thriving in academia, 2024)
To thrive in academia, wellbeing must be understood and nurtured. Recent events such as the COVID-19 pandemic has left the landscape of higher education altered and uncertain, resulting in a range of important considerations which can jeopardise wellbeing and positive mental health of those working within the academic community. Written with a core understanding of wellbeing and the different challenges and stresses on our mental health, this easily digestible and accessible text encourages those in academia to reflect upon how they are functioning, both in and out of the classroom, offering a range of suggestions for smarter ways of working. A deeper discussion threads through on the balance between job satisfaction and life satisfaction, and calls educators and academics to remember why they entered academia in the first place and how to maintain these values in a way that continues to inspire and drive us. Containing 'critical questions', Nurturing Wellbeing in Academia provides useful, practical ideas to help maintain or to recapture a feeling of wellbeing. Topics discussed include applying for promotions, research grants, mentoring, using social media and publishing pressures. This is an ideal resource for those who may be considering transitioning into higher education, helping to prepare them for the challenges and cognitive load that academia can bring.